Design of a Website-Based Waqf Management Information System at the Ansor Waqf Institution in West Java - Miki Wijana; Jalaluddin Jalaluddin; Jajang Suherman; Yusuf Muhyidin (Jurnal Accounting Information System (AIMS), 2026)
Professional, transparent, and accountable waqf management has become an essential requirement for waqf institutions in the digital era. Lembaga Wakaf Ansor Jawa Barat, as a waqf management institution, faces several challenges related to manual and non-integrated data management of waqf donors (wakif), trustees (nazhir), waqf assets, and reporting processes. These conditions may lead to data inconsistency, delays in information delivery, and limited transparency in waqf management. This study aims to design and develop a web-based waqf management information system to support effective and efficient waqf administration. The research method used is Research and Development (R&D) with an Agile approach adapted to the Scrum framework practices. Data were collected through observation, interviews, documentation, and literature study. The system was developed iteratively through several sprints and tested using the Black Box Testing method. The results indicate that the developed system is able to manage waqf data in an integrated manner, generate accurate and timely reports, and improve efficiency and transparency in waqf management. Based on the testing results, all system functionalities operate as expected and the system is considered feasible for implementation. This research is expected to contribute to the development of waqf management information systems and serve as a reference for waqf institutions in adopting information technology in the digital era.